2019
DOI: 10.1016/j.triboint.2019.03.047
|View full text |Cite
|
Sign up to set email alerts
|

Influence of dimple shape on tribofilm formation and tribological properties of textured surfaces under full and starved lubrication

Abstract: Lubrication conditions have significant influences on the formation of tribofilms and then affect tribological behavior. In this work, the influence of tribofilm formation on the tribological behavior of textured surfaces with oval shapes was measured using a pin-on-plate tribometer. The results show that, under full lubrication, the adsorbed oil film controlled the friction and wear behavior of steel/steel tribopairs but under starved lubrication, the formation of a tribofilm significantly influenced the trib… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
34
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 77 publications
(37 citation statements)
references
References 44 publications
(46 reference statements)
3
34
0
Order By: Relevance
“…However, different effects of groove orientation can be obtained for other operating parameters, such as the contact pressure. The authors of papers [ 128 , 129 , 130 , 131 , 132 ] found that ellipsoidal dimples should be positioned perpendicularly to the sliding direction to improve tribological properties. Qiu et al [ 128 ] obtained the highest load-carrying capacity under gas-lubricated sliding for the ellipsoidal oil pockets oriented orthogonally to the direction of motion.…”
Section: Spatial Parametersmentioning
confidence: 99%
See 1 more Smart Citation
“…However, different effects of groove orientation can be obtained for other operating parameters, such as the contact pressure. The authors of papers [ 128 , 129 , 130 , 131 , 132 ] found that ellipsoidal dimples should be positioned perpendicularly to the sliding direction to improve tribological properties. Qiu et al [ 128 ] obtained the highest load-carrying capacity under gas-lubricated sliding for the ellipsoidal oil pockets oriented orthogonally to the direction of motion.…”
Section: Spatial Parametersmentioning
confidence: 99%
“…Lu and Khonsari [ 130 ] obtained better tribological performance of elliptical dimples over circular ones under mixed lubrication. Oval dimples oriented perpendicularly to the sliding direction can lead to a decrease in the coefficient of friction in starved lubrication under reciprocating motion; however, the results depend on the ratio of the major to the minor axes of the ellipse [ 131 ]. The elliptical dimples showed the friction reduction up to 30%; compared with behaviour of untextured specimens in reciprocating motion, squared and circular oil pockets offered a smaller reduction [ 132 ].…”
Section: Spatial Parametersmentioning
confidence: 99%
“…For the reason of micro-reservoirs of lubricating oil, micro-hydrodynamic perturbations (increasing total load carrying capacity) and wear debris trapping roles, surface texture has a significant effect on friction and wear properties, but this effect has various trend under different working conditions. 34 Figure 3 shows the variation trend of friction coefficient with the increase in Hertz contact pressure from 0.819 to 2.00 GPa when the SRs are 5% and 25%, respectively. The friction coefficient decreases with the increase in Hertz contact pressure between the contact surfaces, and this decreasing trend is evident at high entrainment velocity.…”
Section: Analysis Of Test Resultsmentioning
confidence: 99%
“…In the current research, the main consideration for the application of texture is the influence of related parameters, and different texture parameters are designed for different application scenarios. For example, in Xu et al's [32][33][34][35][36] research, the application of different texture parameters in cylinders was studied, and friction and wear tests were carried out on the textured elements using a friction and wear machine. e research results provided a good understanding for the lubrication mechanisms of different textured surfaces.…”
Section: Introductionmentioning
confidence: 99%